Partial pressure of oxygen in adipose tissue and its relationship with fatness in a natural animal model of extreme fat deposition, the grey seal. Issue 16 (19th August 2021) - Oller, Laura; Bennett, Kimberley A.; McKnight, J. Chris; Moss, Simon E.W.; Milne, Ryan; Hall, Ailsa J.; Rocha, Joel
Abstract: Excessive adiposity is associated with altered oxygen tension and comorbidities in humans. In contrast, marine mammals have high adiposity with no apparent detrimental effects. However, partial pressure of oxygen (Po2 ) in their subcutaneous adipose tissue (blubber) and its relationship with fatness have not been reported. We measured Po2 and temperature at different blubber depths in 12 healthy juvenile grey seals. Fatness was estimated from blubber thickness and morphometric parameters. Simultaneously, we monitored breathing pattern; heart rate and arterial blood saturation with a pulse oximeter; and relative changes in total hemoglobin, deoxyhemoglobin, and oxyhemoglobin in blubber capillaries using near‐infrared spectroscopy (NIRS) as proxies for local oxygenation changes. Blubber Po2 ranged from 14.5 to 71.4 mmHg (39.2 ± 14.1 mmHg), which is similar to values reported in other species. Blubber Po2 was strongly and negatively associated with fatness (LME: p  < 0.0001, R 2 marginal = 0.53, R 2 conditional = 0.64, n  = 10), but not with blubber depth. No other parameters explained variability in Po2, suggesting arterial blood and local oxygen delivery did not vary within and between measurements. The fall in blubber Po2 with increased fatness in seals is consistent with other animal models of rapid fat deposition. However, the Po2  levels at which blubber becomes hypoxic and consequences of low blubber Po2 for its health and function, particularly in very fat individuals, remain unknown. How seals avoid detrimental effects of low oxygen tension in adipose tissue, despite their high and fluctuating adiposity, is a fruitful avenue to explore. Abstract : Grey seals blubber Po2 is similar to that measured in other mammal species and negatively associated with fatness, independently of depth of measurement, oxygen delivery, or temperature.